Stylistic variability of the Abashevo ceramics: on the problem statement - Panteleeva S.E. (Вестник археологии, антропологии и этнографии, 2022)
The article presents the results of generalization and systematization of available data on household ceramics of the Abashevo cultural-historical community. This cultural formation extended through the forest-steppe zone of the European part of Russia from the Don Region to the Trans-Urals. The obtained radiocarbon dates comprise the period of 2200–1800 cal BC. The study is based on published information about collections of 33 settlements located in different parts of the vast Abashevo area. The following set of features was considered for comparison: tempering materials, methods of surface treatment, shapes of vessels, main ornamental elements and techniques of their application, and key ornamental compositions. As a result of the analysis, the ceramic collections were divided into seven groups, which can be combined into four large stylistic zones for the similarity of ornamental and morphological characteristics: Don-Volga, Trans-Volga, Cis-Urals, and Trans-Urals. The distribution areas of stylistic zones apparently correspond to the areas of residence of the major local groups of the Abashevo population. It is noted, that addressing the issues of chronological correlation of separate districts and the sites within them is impossible without the implementation of a large-scale program of radiocarbon dating. Stylistic variability of the Abashevo pottery was considered within the framework of the information exchange theory of H.M. Wobst. It has been concluded, that the inhabitants of the Cis-Ural settlements, who had the most diverse and expressive ceramic complex, were involved in active interactions with communities of other regions. A need to demonstrate the group identity was reflected in the appearance of pottery made in a specific style characteristic only for this group. At the same time, external connections initiated diffusion of foreign stylistic features that resulted in increased internal variability of wares. The main reason for the intensive cultural contacts was apparently the specialization of the Cis-Ural communities on metal production. The uniformity and simplicity of pottery from the Don-Volga settlements suggest a high degree of internal integration of the local population, and as a consequence — the absence of necessity for marking the social boundaries between the groups. The external contacts were probably weak, or irregular, and they did not lead to significant changes in the structure of society and diffusion of new stylistic elements. Pottery of the Trans-Ural group appears rather independent, although some of the vessels have specific features of the Abashevo pottery tradition of the western regions. It can be assumed that the Trans-Ural settlements were occupied by a group of people that separated from the main Abashevo massif and advanced beyond the Ural Mountains in search of sources of high-quality ore raw materials. Apparently, these sites are the latest, and they are synchronous to the Sintashta antiquities.